Enhanced photocatalytic activity of Bi25FeO40–Bi2WO6 heterostructures based on the rational design of the heterojunction interface. Issue 31 (9th March 2016) - Zhang, Lei; Zou, Yue; Song, Jian; Pan, Cheng-Ling; Sheng, Shao-Ding; Hou, Chang-Min
Abstract : Based on the rational design of heterojunction interface, a novel and efficient Bi25 FeO40 –Bi2 WO6 heterostructure photocatalyst was successfully constructed by a facile hydrothermal process. Abstract : Based on the rational design of the heterojunction interface, a novel and efficient Bi25 FeO40 –Bi2 WO6 heterostructure photocatalyst was successfully constructed by a facile hydrothermal process, using pre-fabricated Bi2 WO6 nanoflakes as Bi 3+ source and the second-phase material. The as-prepared photocatalyst was characterized by powder X-ray diffraction (XRD), FT-IR spectrum, energy dispersive spectrometry (EDS), X-ray photoelectron spectrum (XPS), high resolution transmission electron microscopy (HRTEM) and scanning electron microscopy (SEM). The photocatalytic performance of the Bi25 FeO40 –Bi2 WO6 heterostructure under the UV-visible light irradiation was investigated, which showed that such Bi25 FeO40 –Bi2 WO6 heterojunctions possessed a higher photocatalytic ability than the mechanical mixing product and the single-phase sample (Bi25 FeO40 and Bi2 WO6 ). This enhanced photocatalytic efficiency might be attributed to the matching band positions, close interfacial connection, and "face-to-face" contact mode of heterojunction interface. In addition, a possible photocatalytic decomposition mechanism and the separation process of photoinduced electrons and holes were discussed at length.